The Effect of Transactional Leadership, Compensation, and Organization Culture on Employee Performance with Work Motivation as a Mediating Variable - Catherin, Febrina Claudia; Ardi, Ardi; Sunarjo, Richard Andre (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
This research investigates how transactional leadership, compensation, and organizational culture at Hotel XYZ influence employee performance, with work motivation playing a role as a mediator. A quantitative approach was employed, involving a questionnaire survey of 110 Hotel XYZ employees in Makassar. Data analysis was conducted using the SEM-PLS technique. The findings suggest that transactional leadership does not have a notable impact on employee performance, but compensation and organizational culture play a significant role. Additionally, it is evident that work motivation serves as a mediator for the relationship between organizational culture and employee performance. This research benefits Hotel XYZ by informing strategies to enhance employee performance through a focus on developing organizational culture and work motivation.